The Use of the Mattampu’ Application to Improve Pregnant Women’s Knowledge of Physiological Changes During Pregnancy - Tahira (Papua Medicine and Health Science, 2025)
Physiological changes during pregnancy often cause discomfort and anxiety in pregnant women, which, if not well understood, may increase the risk of pregnancy complications. This study aims to evaluate the effectiveness of the Mattampu’ application, a locally developed Android-based educational media, in improving pregnant women’s knowledge of physiological changes during pregnancy. A descriptive quantitative design with a one-group pretest–posttest approach was employed. The sample consisted of 90 pregnant women selected through accidental sampling at the Kassi-Kassi Public Health Center, Makassar. The intervention was conducted through the use of the Mattampu’ application, and knowledge levels were measured before and after the intervention using a structured questionnaire. Analysis using the McNemar test revealed a significant increase in knowledge levels across all trimesters: from 26.7% to 73.3% in the first trimester (p=0.001), from 23.3% to 93.3% in the second trimester (p=0.000), and from 23.3% to 90.0% in the third trimester (p=0.000). This study concludes that the Mattampu’ application is effective in enhancing pregnant women’s knowledge of physiological changes during pregnancy and holds potential as an adaptive, contextual, and sustainable model of digital education in antenatal care services.